The Role Of Storytellin In Enhancing Students ‘Understanding Of Verb Tense’ - Radita Yogi Oktaviani; Danang Dwi Harmoko (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study analyzes the effectiveness of storytelling in iproving students’ understanding of English Grammar, particulary verb tenses (simple present, simple past, and simple future tense). Using a quantitative approach with a quasiexperimental design, this study involved seventhgrade students at SMP Bina Bangsa Mandiri 2. The learning moel applied was storytelling-Based Grammar Learning, with the narrative “Squirrel’s Dream House” as the core material. Data collection instruments include written tests (post-test), classroom observations, and retelling assignments. The result of the analysis showed that more than 70% of students experienced a significant increase in their understanding of verb tenses after the implementation of storytelling-based learning. In addition, this method proved to be effective in creasing students’ confidence in speaking, vocabulary acquisition, and classroom participation. These findings indicate that storytelling provides a framework for grammar learning that is not only meaningful and engaging, but also highly contextual, successfully bridging the gap between abstract grammar rules and real communication needs. Therefore, storytelling is recommended as an effective, enjoyable, and holistic grammar teaching strategy, especially in the context of EFL (English as a Foreign Language) classroom.